AGROPEDAGOGICAL COMPETENCIES OF A TEACHER AT AN AGRICULTURAL UNIVERSITY BASED ON THE COMPETENCY-BASED APPROACH - Sultanov Elimbet Kalymbetovich (Modern American Journals, 2025)
In the context of the transformation of agricultural education and the implementation of the competency-based approach, there is an increasing need to rethink the professional competencies of teachers at agricultural universities. This article analyzes the structure of agropedagogical competencies, their specific features, and the ways in which they are formed in the context of modern educational requirements.
Keywords: Agropedagogical competencies, Agricultural education, Competency-based approach, Professional development, Digital technologies in agriculture, Virtual learning environment, Simulation and 3D modeling, Mechanization of agriculture, Integration of theory and practice, Research competencies.